Admission indications, initial diagnoses, Interventions, and patient outcomes within the sole obstetric high-dependency unit in Ethiopia - Zewdu Beza; Roza Tadesse; Henok Teshome; Genetu Tadele; Melkamu Siferih (BMC, 2024)
Abstract Background Obstetric high-dependency care offers holistic care to critically ill obstetric patients while maintaining the potential for early mother-child bonding. Little is known about the obstetric high-dependency unit (HDU) in Ethiopia. Therefore, the objective of the study was to review the admission indications, initial diagnoses, interventions, and patient outcomes in the obstetric high-dependency unit at St.Paul's Hospital. Methods A retrospective observational study was carried out at St. Paul's Hospital in Addis Ababa, Ethiopia, between September 2021 and September 2022, targeting patients in the obstetric high-dependency unit during pregnancy or with in 42 days of termination or delivery. A checklist was used to compile sociodemographic and clinical data. Epidata-4.2 for data entry and SPSS-26 for data analysis were employed. Chi-square tests yielded significant results at p < 0.05. Result Records of 370 obstetric patients were reviewed and analyzed. The study enlisted participants aged 18 to 40, with a mean age of 27.6 ± 5.9. The obstetric high-dependency unit received 3.5% (95% CI, 3.01-4.30) of all obstetric admissions. With the HDU in place, only 0.42% of obstetric patients necessitated adult intensive care unit (ICU) admission. The predominant motive behind HDU admissions (63.2%) was purely for observation. Hypertensive disorders of pregnancy (48.6%) and obstetric hemorrhage (18.9%) were the two top admission diagnoses. Ten pregnant mothers (2.7%) were admitted to HDU: 2 with antepartum hemorrhages, and 8 with cardiac diseases. Maternal mortality and transfer to the ICU were both 1.4 per 100 HDU patients. Conclusion Our study found that the most frequent indication for admission to the HDU was just for observational monitoring. Hypertensive disorders of pregnancy and obstetric hemorrhage were the two leading admission diagnoses. Expanding HDUs nationwide is key for mitigating the ICU burden from obstetric admissions. Strategies for early prenatal screening, predicting preeclampsia, and addressing postpartum hemorrhage should be reinforced. Future studies should focus on a broader array of factors affecting fetomaternal outcomes in such a unit.